TINJAUAN SOSIO KRIMINOLOGIS TERHADAP KEBIASAAN MEMILIKI DAN MEMBAWA SENJATA TAJAM OLEH MASYARAKAT PULAU KALEDUPA KABUPATEN WAKATOBI - Samaluddin Samaluddin; Hardi Done; Sumardin Sumardin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
This study aims to determine the factors that influence the habits of the people of Kaledupa Island, Wakatobi Regency to have and carry sharp weapons in association and the efforts that can be made by policy makers in overcoming them. Sociological juridical research method.descriptive research specifications. Primary data sources are the results of interviews with resource persons and observations as well as secondary data sources in the form of the Criminal Code (KUHP), Emergency Law Number 12 of 1951 concerning firearms, Law Number 2 of 2002 concerning the Indonesian National Police, literature books and internet articles related to the aspects studied. Methods of collecting data with interviews and observations as well as literature study. form of data presentation in narrative text and tables, qualitative data analysis. Based on the results of research and discussion of the subject matter proposed in this thesis, it can be concluded that the factors that influence the habits of the people of Kaledupa Island, Wakatobi Regency to have and carry sharp weapons in the struggle are the low level of education, misinterpretation of the existence of BharataKaledupa as one of the factors that influence the existence of BharataKaledupa. bharata at the time of the Sultanate of Buton, there was omission by certain parties. Efforts that can be made by policy makers in overcoming the habits of the people of Kaledupa Island, Wakatobi Regency in making sharp weapons in association are community leaders on Kaledupa Island who can create an institution for fostering the younger generation to carry out social activities, activating youth youth activities and legal counseling and the police do not only carry out preventive and repressive efforts in an effort to overcome the habit of people carrying sharp weapons but also must make pre-emptive efforts.